HUBUNGAN ANTARA MOTIVASI KERJA TERHADAP KOMITMEN KARYAWAN - Putri Najzwa Maulida; Tri Wahyuni; Sulislistiasih (Jurnal Ekonomi dan Bisnis, 2024)
Work motivation is one of the key factors that influences employee performance and commitment in the organization. This research aims to analyze how increasing work motivation can influence the level of employee commitment to the company. The methodology used includes qualitative analysis through analysis of employees from various industries, as well as qualitative analysis through in-depth interviews to gain deeper insights. The research results show that factors such as financial rewards, recognition from management, career development opportunities, and a positive work environment have a significant positive correlation with work motivation. Furthermore, this increase in motivation has been proven to increase employee commitment, which is characterized by increased loyalty, reduced turnover rates, and increased employee participation in organizational activities.